Sleep quality among adult patients with chronic dermatoses - Kaaz, Karolina; Szepietowski, Jacek; Matusiak, Łukasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Chronic dermatoses, including atopic dermatitis, psoriasis, prurigo nodularis, chronic spontaneous urticaria and hidradenitis suppurativa, as well as accompanying subjective symptoms (itch and pain), have a great impact on patients’ well-being. Skin plays an important role in the physiological sleep process. This review attempts to analyze the association between chronic dermatoses in adults and sleep quality in recent studies. Polysomnography and actigraphy are performed for the objective assessment of sleep quality. Questionnaire-based subjective evaluations of sleep quality, including the Pittsburgh Sleep Quality Index and Medical Outcomes Study Sleep Scale, are useful in clinical studies and clinical practice. Subjective symptoms such as itch and pain have an essential influence on sleep quality and general quality of life in patients with chronic skin diseases.